Pengaruh Lingkungan terhadap Produktivitas Kelapa Sawit di Afdeling III Kebun Bah Birung Ulu PT Perkebunan Nusantara IV Regional II - Muhammad Iswan; Aulia Juanda Djaingsastro; Saroha Manurung (Dinasti Research, 2026)
This study aims to analyze the influence of environmental factors on oil palm productivity in Afdeling III Bah Birung Ulu Plantation, PT Perkebunan Nusantara IV Regional II. The environmental factors studied include rainfall, air temperature, relative humidity, and sunlight intensity. The study was conducted in February–March 2026 using a qualitative descriptive method with primary and secondary data collection. Environmental data were obtained through field measurements using a thermohygrometer and lux meter, while productivity data were obtained from plantation production archives. Plant productivity was measured based on the weight of fresh fruit bunches (FFB) per hectare. The results showed that the average rainfall at the study site reached 3,579.8 mm/year with an average of 147.9 rainy days/year. Air temperature ranged from 23–28°C, relative humidity was in the range of 68–92%, and sunlight intensity ranged from 1,367–3,121 lux. The highest productivity was recorded in the 2008 planting year at 2,184 kg/ha, while the lowest productivity was in the 2006 planting year at 1,026 kg/ha. Sunlight intensity is an environmental factor strongly suspected of influencing oil palm productivity because it plays a direct role in the photosynthesis process. Plant age also influences oil palm productivity. Further research is recommended to consider other factors such as soil conditions, fertilization, and cultivation management to obtain a more comprehensive productivity model.